Standards of Care in Global Health: Identifying the Right Question - Ndebele, Paul (The Hastings Center report, 2017)
Govind Persad and Ezekiel Emanuel's article “The Case for Resource Sensitivity: Why It Is Ethical to Provide Cheaper, Less Effective Treatments in Global Health,” in this issue of the Hastings Center Report, is a reminder of the debates around resources for health care that raged during the years immediately preceding and following the fifth revision of the Declaration of Helsinki, in 2000. In global health, it is a common expectation for rich countries to assist poor countries in resolving health challenges, yet global health involves not only the governments of rich and poor nations but also nongovernmental organizations, pharmaceutical companies, the World Health Organization, philanthropic organizations, and other parties—all of whom take roles in ensuring that health interventions become available to poor countries, including deciding which types of interventions to make available. The question whether it is ethical to provide cheaper, less effective interventions to poor countries is perhaps relevant only in wealthy nations, where there really is a choice to be made.